Tombusvirus p19 Captures RNase III-Cleaved Double-Stranded RNAs Formed by Overlapping Sense and Antisense Transcripts in Escherichia coli - Linfeng Huang (American Society for Microbiology, 2020)
ABSTRACT Antisense transcription is widespread in bacteria. By base pairing with overlapping sense RNAs, antisense RNAs (asRNA) can form double-stranded RNAs (dsRNA), which are cleaved by RNase III, a dsRNA endoribonuclease. The ectopic expression of plant Tombusvirus p19 in Escherichia coli stabilizes ∼21-nucleotide (nt) dsRNA RNase III decay intermediates, which enabled us to characterize otherwise highly unstable asRNA by deep sequencing of p19-captured dsRNA. RNase III-produced small dsRNA were formed at most bacterial genes in the bacterial genome and in a plasmid. We classified the types of asRNA in genomic clusters producing the most abundant p19-captured dsRNA and confirmed RNase III regulation of asRNA and sense RNA decay at three type I toxin-antitoxin loci and at a coding gene, rsd. Furthermore, we provide potential evidence for the RNase III-dependent regulation of CspD protein by asRNA. The analysis of p19-captured dsRNA revealed an RNase III sequence preference for AU-rich sequences 3 nucleotides on either side of the cleavage sites and for GC-rich sequences in the 2-nt overhangs. Unexpectedly, GC-rich sequences were enriched in the middle section of p19-captured dsRNA, suggesting some unexpected sequence bias in p19 protein binding. Nonetheless, the ectopic expression of p19 is a sensitive method for identifying antisense transcripts and RNase III cleavage sites in dsRNA formed by overlapping sense and antisense transcripts in bacteria.